Lexical dominant in the story of Mykola Khvyliovyi “Sanatorium zone” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyzes the vocabulary of Mykola Khvyliovyi, in view of its constant domination and repetition of separate lexemes in the text. The semantic features and functional role of lexical dominant in the story “Sanatorium zone” are revealed; their structural and stylistic peculiarities of author's conception of reality transmission are investigated: their linguistic aspect is traced as verbalizers of stylistic figures of “silence” and “scream”. The author uses lexemes that characterize the figure of silence “Anarch of Stupid”, “Maya nervously shrugged his head and silently rushed forward”, “River was silent. But even in the silence of the river was the same indescribable loneliness”. Mykola Khvylovy uses tokens on the sign of silence to relate the silence of Man and Nature. The words of silence are used by them in the works “Mother”, “Silhouettes” and others. In the final story, the scream turns into mute pain. It goes down inside the heroes. Consequently, the lexical dominant is a phenomenon, which in the text of the story acquires poly-dimensional significance, forms the concept sphere and expresses the attitude of the author. M. Khvylov's statement of his position is achieved precisely because of the saturation of the text of the story with dominant lexemes, which give the author's style polysemic, expressiveness and individuality. The Ukrainian prose of the 20-30's of the twentieth century represented the peculiarity of the image of mental processes determined by social circumstances on the basis of post-revolutionary activity. Logically, in this typological context, the stories of Mykola Khvylovyy with their lexical dominantes, which determine the originality of his style and the poetics of the work of art, fit into it. The term “dominant” is used in the theoretical interpretation of the prominent neurophysiologist, psychologist and neurologist O. Ukhtomsky.
Keywords: lexical dominant; lexeme; microderminant; stylistic peculiarity; verbalizer